Measuring the Efficacy of Interactive Flipbooks in Boosting Reading Interest: Evidence from a Systematic Literature Review - Kurnianingsih, Sri; Muhimmah, Hitta Alfi; Siswanto, M. Bambang Edi (Jurnal Paedagogy, 2026)
This study aims to examine the effectiveness of interactive flipbook media in enhancing elementary school students’ reading interest. A systematic literature review was conducted following PRISMA guidelines. Relevant studies were retrieved from Scopus, Web of Science, ERIC, Google Scholar, and Consensus AI databases. Data were analyzed using descriptive statistical synthesis and thematic analysis to identify implementation patterns and student outcomes. The results indicate that interactive flipbook media consistently produces significant positive effects on students’ reading interest, with reported improvements ranging from 11% to 32% across studies. The media is particularly effective in enhancing visual literacy, digital literacy, and cultural appreciation, alongside traditional reading skills. However, several implementation challenges were identified as barriers to widespread adoption. This review concludes that interactive flipbooks represent a promising pedagogical tool for elementary education. Successful implementation, however, requires adequate technological infrastructure, comprehensive teacher training, and further research across diverse educational contexts and subject areas.